Zaleznosc wskazników sily miesni zginaczy i prostowników konczyn dolnych u lekkoatletów - sprinterów o róznym poziomie zaawansowania - Juszkiewicz, T.; Starosta, W. (Medycyna sportowa, 2000)
Although muscle strength has been widely researched, there are no reports concerning the relationships between strength indices of flexors and extensors of lower limbs of sprinters differing in performance and this subject constituted the aim of the study. Measurements of maximal strength of various muscle groups of lower limbs were conducted according to Rybalko (1966). These measurements were taken in the following order: thigh, shank, and feet. The research involved 125 sprinters of various levels of advancement: from beginners (n = 25) to champions (n = 16), including members of the National Team of Belarus and 12 boys aged 9-10 years. It was found that one of the reasons of a reduced maximum frequency of steps during the run of advanced sprinters, as compared to the 9-10 year old boys, was a distorted relationship between extensors and flexors of lower limbs. The relations between strength indices of extensors and flexors of the thigh, shank and foot of boys aged 9-10 years approximated those of champion class sprinters. High sprint achievements are frequently hampered by the relatively weak muscle groups (mainly the flexors of the thigh, shank, and the foot), which "participate to a limited extent", and are therefore less loaded in the training process.